Duality for Toeplitz Extensions - Schulz-Baldes, Hermann; Stoiber, Tom (Springer, 2022)
Let (A, G, ξ) be a C∗ -dynamical system, where A is a separable C∗ -algebra and G= R or G= T. This section will relate A and A⋊ ξG in an exact sequence of C∗ -algebras and then show a duality for pairings of cyclic cocycles with Kj(A) respectively Kj + 1(A⋊ ξG).
CRIS-Team Scopus Importer:2024-12-16